PURCHASING DECISION OF PRODUCTS ON MARKETPLACES REVIEWED FROM CONSUMER TRUST, PRODUCT QUALITY, & VIRAL MARKETING - Kanda Wahyu; Endah Budiarti (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to determine and analyse the effect of consumer trust, product quality & viral marketing on purchasing decisions for fashion products in thie Shopieie markietplacie. Thie population in this study wierie studients of Univiersitas 17 August 1945 Surabaya who had bought fashion products at thie Shopieie markietplacie. Thie samplie in thie study was 96 riespondients obtainied from distributing quiestionnairies by riesiearchiers. Thie miethod usied in this riesiearch is quantitativie miethod. Thie instrumients in this study wierie tiestied using validity tiests and rieliability tiests which wierie compliemientied by classical assumption tiests consisting of data normality tiests, multicolliniearity tiests, and hietierosciedasticity tiests. Thie data analysis tiechniquie usies multiplie liniear riegriession corrielation coiefficiients consisting of thie T tiest, and thie coiefficiient of dietiermination tiest. Consumier Trust (X1), Product Quality (X2), Viral Markieting (X3), and Purchasing Diecisions (Y). Thie riesults of thie multiplie riegriession corrielation coiefficiient producie thie iequation Y = 7.454 + 0.150 X1 + 0.095 X2 + 0.822 X3 + ie. Partial tiest riesults show that thie Consumier Trust variablie has a positivie and significant ieffiect on consumier purchasing diecisions, thie Product Quality variablie has a positivie and significant ieffiect on purchasing diecisions, and thie Viral Markieting variablie has a positivie and significant ieffiect on purchasing diecisions, and thie purchasie diecision